2019
DOI: 10.1080/14756366.2019.1697251
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase IX as a novel candidate in liquid biopsy

Abstract: Among the diagnostic techniques for the identification of tumour biomarkers, the liquid biopsy is considered one that offers future research on precision diagnosis and treatment of tumours in a non-invasive manner. The approach consists of isolating tumor-derived components, such as circulating tumour cells (CTC), tumour cell-free DNA (ctDNA), and extracellular vesicles (EVs), from the patient peripheral blood fluids. These elements constitute a source of genomic and proteomic information for cancer treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…The CA superfamily is grouped into eight genetically distinct families (or classes), named with the Greek letters α, β, γ, δ, ζ, η, θ, and ι [13][14][15]30,31]. In mammalian, for example, 15 CAs are expressed, 12 of which are catalytically active, and all belong to the α-class [9,16,[32][33][34][35][36][37]. It is interesting to stress that the genome of most pathogens does not encode for a α-CA [12][13][14]34,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…The CA superfamily is grouped into eight genetically distinct families (or classes), named with the Greek letters α, β, γ, δ, ζ, η, θ, and ι [13][14][15]30,31]. In mammalian, for example, 15 CAs are expressed, 12 of which are catalytically active, and all belong to the α-class [9,16,[32][33][34][35][36][37]. It is interesting to stress that the genome of most pathogens does not encode for a α-CA [12][13][14]34,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, many pharmaceutical uses have notable goals for a variety of CA isoforms, including antiglaucoma drugs, anticonvulsant factors/diagnostic, diuretics, antiobesity, and antitumor tools [ 59 , 60 ]. For instance, inhibitors of the hCAs IX and XII isozymes have been used as antitumor and antimetastatic agents [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have reported the relationship between CA-IX and sEVs in different cancer types [ 44 , 45 , 46 , 47 ]. For the first time, we investigated CA-IX protein expression associated with sEVs in melanoma in vitro models.…”
Section: Introductionmentioning
confidence: 99%